Investigation into Cryptosporidium and Giardia in bivalve mollusks farmed in Sardinia region and destined for human consumption - Tedde T.; Piras G.; Salza S.; Nives R. M.; Sanna G.; Tola S.; CULURGIONI, Jacopo; Piras C.; Merella P.; Garippa G.; Virgilio S. (Italian Journal of Food Safety, 2013)
"Cryptosporidium and Giardia are protozoan parasites transmitted by fecal-oral ingestion of (oo)cysts, and are responsible for enteritis in several animal species and humans worldwide. These (oo)cysts can survive for over a year in aquatic environments and can accumulate in bivalve mollusks, which filter large volumes of water. The aim of this study is to evaluate the natural occurrence of Cryptosporidium and Giardia contamination in different specimens of edible bivalves mollusks from farming sites of the western and north-eastern coasts of Sardinia. From April 2011 to February 2012, 1095 specimens of Mytilus galloprovincialis and 240 of Crassostrea gigas were sampled from Olbia and Oristano gulf and San Teodoro pond. Hepatopancreas and gills, including the labial palp, were examined for oocysts and cysts after pooling and homogenisation using different techniques: i) staining for light and fluorescence microscopy; ii) direct immunofluorescence (IF) Merifluor® test Cryptosporidium/ Giardia (Meridian Bioscience Inc., Cincinnati, OH, USA); and iii) molecular procedures. However, in the context under study, all mollusks examined with the three main diagnostic techniques were negative for both parasites pointing out the hypothetically low zoonotic risk related to Cryptosporidium and Giardia in bivalves, especially Mytilus galloprovincialis and Crassostrea gigas"